Answer:
The inverse function of f(x) is
Explanation:
Given function as :
f(x) = 2 x + 37
Let The inverse function of f(x) =
![f^(-1)x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/18ogdvzxoodjl4kbc5ehxp411d0p514qa8.png)
or, y = 2 x + 37
Now, swap x and y variables
So, x = 2 y + 37
Again, solve for y
i.e 2 y = x - 37
or, y =
![(\textrm x - 37 )/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6eo6r9wq4myahknr78gkwn29eve1cilv36.png)
∴
= y =
![(\textrm x - 37 )/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6eo6r9wq4myahknr78gkwn29eve1cilv36.png)
Or,
=
![(\textrm x - 37 )/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6eo6r9wq4myahknr78gkwn29eve1cilv36.png)
Hence The inverse function of f(x) is
Answer